Ações afirmativas na universidade popular brasileira: o caso da universidade federal do sul da Bahia - UFSB - Nóbrega, Evangelita Carvalho da (2016)
This research deals with affirmative actions in Brazilian popular university the case of the Federal University of Southern Bahia (UFSB), regarding the process of access and permanence. The research developed from exploratory research and documentary study. Therefore, the theoretical framework was based on the correlations between the Brazilian university, the popular University and affirmative actions for access and retention policies. In the analysis phase, official documents from UFSB were used, all selected and removed from the university's website, which are: the guiding plan, the founding charter and the statute, the selection process notices of entry, the permanence support scholarship notices, resolutions, student manual, and the management report selected between 2014 to 2015. In order to analyze the research object, it was applied in the documentary study and systematic observation. For the analysis of the phenomenon, it earned a qualiquantitative approach, using the content analysis technique. Thus, it was found that the UFSB presents an innovative proposal to current models of universities. Apparently, this institution seeks to make a commitment to social inclusion policies, which runs through the internalization of access, deployment of CUNIs as integration and inclusion space, the implementation of the reservation policy positions and political quotas, and the adoption of policy to support retention of students. The percentage of adopted vacancies reserve was higher than expected in the Federal Law No. 12.711 / 12, or over 55% of the vacancies, covering various identity categories: public school graduates, low-income, black self-declared, brown or indigenous (PPI) and others. This indicates social inclusion through access policy. About the permanence, it was found that adopted permanence policies refers only to some programs / projects of limited scope in partnership with federal agencies, therefore, still in the embryonic stage, with the predominance the student assistance through the Support Permanence Program (PNAES), with scholarships and financial aid for students in socioeconomic vulnerability. However, it should be taken into consideration that the UFSB is in construction process, adapting and testing their innovations. In this sense, it is a challenge to the implementation of the Permanent Support Program, it seems, since there are not enough resources available for higher level educational institution (IES, in Portuguese) ensure that policy. Thus, it is considered that social inclusion, at this university, is the result of affirmative actions policies, and It is a confrontation against social, economic, cultural and territorial inequalities. It is expected that the model under construction by UFSB can be effective as a popular university, democratic, inclusive and integration.